(untitled) (Jurnal EurekaMatika, 2020)
The objective of this research is to analyze data on Quranic memorization ability, obtained from tahfizh examination results using a test instrument, and analyzed using a truncated regression model. Given the restrictions on the dependent variable’s values and that the independent variables are only observed when the dependent variable is observed, the analysis utilizes a doubly truncated normal distribution. In the regression model for this data, the values of the dependent variable are q<Yi​<r, where the observed data lies between point q as the lower bound (a value of 44) and point r as the upper bound (a value of 96). The method used to estimate parameters in the model is the Maximum Likelihood Estimation (MLE) method using the Newton-Raphson iterative process. Data analysis was conducted by determining the linear regression model and the doubly truncated regression model, followed by normality assumption tests and partial coefficient tests for the doubly truncated normal distribution model. The results obtained from this study are a regression model that describes the relationship between tahfizh exam scores, tahsin scores, and final grades. Keywords: Doubly truncated normal distribution regression model, Quranic memorization ability ABSTRAK Tujuan dari penelitian ini adalah untuk menganalisis data kemampuan menghafal Alquran yang datanya diperoleh dari hasil ujian tahfizh menggunakan sebuah instrumen tes, dan digunakan model regresi terpotong. Dilihat dari pembatasan nilai pada variabel dependennya dan variabel independennya hanya akan diobservasi jika variabel dependennya diobservasi, analisis yang digunakan adalah distribusi normal terpotong atas bawah. Model regresi untuk data ini, nilai-nilai variabel dependennya berupa q < Yi < r dimana data yang diobservasi berada diantara titik q yang merupakan batas bawah yaitu nilai 44 dan titik r merupakan batas atas yaitu nilai 96 dari data dependen yang diobservasi. Metode yang digunakan untuk menaksir parameter dalam model adalah metode kemungkinan maksimum dengan menggunakan bantuan iteratif Newton Raphson. Analisis data dilakukan dengan menentukan model regresi linear dan model regresi untuk data terpotong atas bawah, kemudian uji asumsi normalitas serta uji koefisien secara parsial model regresi untuk data berdistribusi normal terpotong atas bawah. Hasil yang diperoleh dari penelitian ini yaitu model regresi yang menggambarkan hubungan antara nilai ujian tahfizh, nilai tahsin, dan nilai akhir.